Cidades rebeldes, efervescentes e educadoras: em Caxias do Sul/RS, quanto de passado existe em nosso presente? - Comarú, Itamar Ferretto (My University, 2021)
When problematizing a document from the 1950s in which certain actions of xenophobia and racism were perceived by some barber shops in Caxias de Sul, another point would be noticed: there would be, there, an apparent network of restrictions that would limit both the flow and access to certain spaces of the contemporary city. In common between past and contemporary tensions, there would be the similarity of subjects subject to intolerance, oppression or humiliation and their places of origin. Based on the indicative paradigm and the theoretical assumptions of cultural history, the study realizes, through the analysis of local historicity and its memory spaces, the possibility of tensioning an instigating social and pedagogical force against conflicting generalizations, exclusions and social deletions perceived there. The city is memory, history and life. It is, above all, dynamism, movement and human representation, whether collective or individual. Therefore, it can also present the most diverse structures of oppression and invisibility, sometimes sedimented both in its educational spaces and in the presentation / representation of memories or flows in constant transformation. The historicity that I present throughout my study emphasizes traditional memory when perceiving the educational potential of cities as a link with contemporary education; an education that ventures through the city, willing to illuminate the shadow areas in which social exclusions are accommodated and to expand the volume of polyphonies that are sometimes not seen or heard; worrying education before social establishment, challenging inequalities. Thus, I consider that my thesis arises inseparable from the historicity that makes up the space, an object of reflection in the face of the human actions and decisions developed there, with remarkable reflections both in the relationship between its citizens and with the products or cultural spaces of representation resulting from it. such decisions. Thus, when considering the historical processes of formation and transformation of the city of Caxias do Sul, the human flow and the existing sociability, the democratic use of the city and its cultural facilities and, finally, the social and pedagogical challenges observed both in the In the urban daily life and in the school field of the city, I consider that the general objective of my thesis is to contribute to a greater understanding of the city as an educational possibility, enhancing the relationships between the pedagogical, historical, social and cultural fields of the city. the city of Caxias do Sul / RS, with its effervescent ruptures and / or ruptures. The thesis that guides my research is that the historicity perceived there reveals an impacting network of educational actions and representations before certain social groups, especially those identified as peripheral, sometimes highlighted as having a lower social, political or symbolic capital in relation to the representations dominant social Therefore, such actions show an important weakness as an Educating City, which is inserted in a complex context of impotence over certain social fields and cultural spaces of society. I believe that reflecting on such historicity and its consequences makes it possible to think of the city in the midst of educational tensions far from the traditional countryside, which configures it as a high-power educator in the face of historical and contemporary problematization, such as such exclusions and invisibilities that tend to social and cultural diversity. and ethnic groups are visible from the beginning of the colonization of space to the present [resumo fornecido pelo autor].
Ao problematizar um documento da década de 1950 em que se se faziam perceber determinadas ações de xenofobia e racismo desenvolvidas por algumas barbearias de Caxias de Sul, um outro ponto seria percebido: haveria, ali, uma aparente rede de restrições que limitaria tanto o fluxo quanto o acesso a determinados espaços da cidade contemporânea. Em comum entre as tensões pretéritas e contemporâneas ter-se-ia a similaridade dos sujeitos submissos às intolerâncias, opressões ou humilhações e os seus locais de origem. Valendo-me do paradigma indiciário e dos pressupostos teóricos da história cultural, o estudo percebe, por meio da análise da historicidade local e de seus espaços de memória, a possibilidade de se tensionar uma instigante força social e pedagógica contra as conflitantes generalizações, exclusões e apagamentos sociais ali percebidos. A cidade é memória, história e vida. Ela é, acima de tudo, dinamismo, movimento e representação humana, seja ela coletiva ou individual. Logo, também pode apresentar as mais diversas estruturas de opressão e invisibilidade, por vezes sedimentadas tanto em seus espaços educativos quanto de apresentação/representação de memórias ou de fluxos em constante transformação. A historicidade que apresento ao longo de meu estudo tensiona a memória tradicional ao passo que percebe o potencial educativo das cidades como elo para a educação contemporânea; uma educação que se aventure pela urbe, disposta a iluminar as zonas de sombra em que se acondicionam as exclusões sociais e ampliar o volume das polifonias que, por vezes, não são vistas ou ouvidas; uma educação perturbadora perante o estabelecido social, desafiadora das desigualdades. Assim, considero que minha tese surge indissociável da historicidade que compõe o espaço, objeto de reflexão perante as ações e decisões humanas ali desenvolvidas, com reflexos contundentes tanto na relação entre seus cidadãos quanto com os produtos ou espaços culturais de representação decorrentes de tais decisões. Assim, ao considerar os processos históricos de formação e transformação da cidade de Caxias do Sul, o fluxo humano e as sociabilidades existentes, o uso democrático da cidade e de seus equipamentos culturais e, por fim, os próprios desafios sociais e pedagógicos observados tanto no cotidiano urbano quanto no campo escolar da cidade, considero que o objetivo geral da minha tese é contribuir para um maior entendimento da cidade como possibilidade educadora, potencializando as relações entre os campos pedagógico, histórico, social e cultural da cidade de Caxias do Sul/RS, com suas efervescentes continuidades e/ou rupturas. A tese que orienta minha pesquisa é a de que a historicidade ali percebida desvela uma impactante rede de ações e representações deseducadoras perante determinados grupos sociais, especialmente àqueles identificados como periféricos, por vezes destacados como detentores de um capital social, político ou simbólico inferior frente às representações sociais dominantes. Logo, tais ações evidenciam uma importante fragilidade enquanto Cidade Educadora, que se vê inserida em um complexo contexto de impotência sobre determinados campos sociais e espaços culturais da sociedade. Considero que refletir sobre tais historicidades e suas decorrências possibilita pensar a cidade em meio a tensões educacionais desviantes ao campo tradicional, o que a configura como educadora em uma potência elevada frente à problematização histórica e contemporânea, pois tais exclusões e invisibilidades que tencionam a diversidade social, cultural e étnica ali existente fazem-se perceber desde os primórdios da colonização do espaço até o tempo presente [resumo fornecido pelo autor].
Keywords: Educação - História - Caxias do Sul (RS); Exclusão social; Education - History - Caxias do Sul (RS); Marginality, Social